Accumulation of Microplastics on Seagrass Leaves of Enhalus acoroides on Mare Island as a Conservation Area in North Maluku - Ramili, Yunita; Umasangaji, Halikuddin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Seagrass ecosystems have been indicated as the new hotspots of microplastics (MPs) in the marine environment. This work aimed at determining the potential of microplastics and epibionts accumulation on Enhalus acoroides leaves at the coast of Mare Island as one of the conservation areas in North Maluku region. Samples collection was carried out in August 2021 at two research locations, namely Maregam (Station 1) and Marekofo (Station 2) villages. Each of E. acoroides leaves (18 leaves) was observed for the presence of microplastic that attached on the epibionts of seagrasses. Seagrass leaves were collected using line transect which was stretched out to 50 m vertically seaward. Subsequently, the characterization of epibionts on the seagrass leave were determined according the rank of the cover percentage of epibionts. Meanwhile microplastics were identified referring to their shapes and colors under microscope observation. The results showed that three types of microplastics were embedded on the epibiont matrices of E. acoroides leaves namely fibers, fragments, and pellets. The average number of microplastic particles in E. acoroides leaves at station 1 was higher (9.1 MPs particles/leaf) than Station 2 (4.5 MPs particles/leaf). The accumulation of fiber type was higher at station 2 (76%) than station 1 (41%), conversely the accumulation of fragment type was higher at Station 1 (54%) than station 2 (19%), while pellets were found to be the least in both stations. Overall, seven colors of microplastic were found, namely blue, brown, black, red, green, orange and white, except at station 2 was absence of brown one. Station 1 was dominated by the white color (32%) while station 2 dominated by the black color (32%). According to the level of epibiont closure, it was found that the presence of microplastics was higher in the rank 1 epibiont at Station 1 where the epibiont covers less than 25%, while at station 2 was the highest one with the rank of 3 which meant that the epibiont covers was 50 – 75%. We concise that through this finding the society should be aware of microplastics extention on coastal area including seagrass leaves. Thus, the local government should pay attention of plastic debris management in the future to mitigate the impacts of these contaminants to the marine environment.Keywords: microplastics, Enhalus acoroides, epibiont, Mare Island